Pengaruh Fraud Triangle Terhadap Kecurangan Laporan Keuangan Pada Perusahaan Perbankan di Bursa Efek Indonesia - Anista, Yesi; Vonna, Sari Maulida; Risnafitri, Hafizhah; Amri, Abrar; Hastuti, Cut Sri Firman (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to examine the effect of the fraud triangle on fraudulent financial statements in banking companies listed on the Indonesia Stock Exchange in 2020 - 2024This study uses the Beneish M-Score to calculate financial statement fraud. The population in this study were Banking companies listed on the IDX used purposive sampling method so that a sample of 10 companies was obtained with 5 years of observation with 50 observations. The analysis technique used in this research is logistic regression model. The results showed that financial stability, external pressure, personal financial need and auditor change had no effect on fraudulent financial statements while ineffective monitoring had an effect on fraudulent financial statements. This study provides evidence that strict supervision by the OJK and BI is an important factor that weakens the relevance of several fraud triangle indicators, thus enriching the literature that regulatory effectiveness can modify the relationship between the fraud triangle and fraud. Keywords: Beneish M-Score, financial statement fraud, fraud triangle.